The need analysis for computational chemistry based learning media atomic structure and chemical bonding basic chemistry courses - Asep Wahyu Nugraha; Marudut Sinaga; Ayi Darmana; Ani Sutiani; Nisa Qurrata Aini (Jurnal Pendidikan Kimia, 2024)
The aim of this research is to analyze students' needs for computational chemistry-based learning media on atomic structure and chemical bonding in the Basic Chemistry course. The population of this study were the first grade students of the Chemistry Department, FMIPA Unimed. The number of samples in this study was 93 students from three classes. The instruments used are multiple choice questions and questionnaires to determine mastery of atomic structure and chemical bonding. The research results show that the average score is 34.430 (poor category). The average score achieved in atomic structure material was 33.16 (very poor). The lowest score achieved in the atomic properties sub-material was 9.3. The average score achieved in chemical bonding material was 36.1 (very poor). The lowest score achieved in the properties of ionic compound sub-material was 17.5. The results of the questionnaire showed that the atomic structure material that students considered the most difficult was the wave mechanics atomic model at 72.233 (quite difficult), while for chemical bonding material it was the octet and duplet rule at 71.055 (quite difficult).